Synthesis of Novel Oxime and Oxime Derivatives Phosphazenes from Hexachlorocyclotriphosphazene - Ozen, Furkan; Cil, Erol; Arslan, Mustafa (CHEM SOC PAKISTAN, 2012)
The new spirocyclophosphazene 2,2-bis(4-benzoylphenoxy)-4,4,6,6 bis[spi-ro(2',2 ''-dioxy-1',1 ''-biphenyl]cyclotriphosphazene (3) was synthesized from the reaction of 2,2-dichloro4,4,6,6-bis[spiro(2',2 ''-dioxy-1',1 ''-biphenyl]cyclotriphosphazene (2) with 4-hydroxybenzophenone. The novel oxime-cyclophosphazene containing 2,2'-dioxybiphenyl groups (4) was synthesized from the reaction of 3 with hydroxlaminehydrochloride in pyridine. The reactions of 4 with methyl iodide, benzyl chloride, acetyl chloride, benzoyl chloride, 4-methoxybenzoyl chloride, 2-chlorobenzoyl chloride, propanoyl chloride, 2-bromoethanol and chloroacetyl chloride were studied. Disubstituted compounds were obtained from the reactions of 4 with methyl iodide, benzyl chloride, acetyl chloride, benzoyl chloride, 4-methoxybenzoyl chloride, 2-chlorobenzoyl chloride and propanoyl chloride. Pure and defined products could not be obtained from the reaction of 4 with 2-bromoethanol and chloroacetyl chloride. All products were generally obtained in high yields. The structures of the compounds were defined by elemental analysis, IR, H-1, C-13 and P-31-NMR spectroscopy.
Keywords: Hexachlorocyclotriphosphazene; phosphazene; oxime; oxime derivatives; oxime-phosphazene; DICHLOROPHOSPHORYL-P-TRICHLOROPHOSPHAZENE; THERMAL-PROPERTIES; POLY(ORGANOPHOSPHAZENES); COMPLEXES; BACTERIAL; POLYMERS; ALKYL; POLYPHOSPHAZENES; PHENOLYSIS; CLEAVAGE; Chemistry